ANALISIS PENGARUH PROMOSI DIGITAL DAN DISKON LOYALITAS TERHADAP MINAT BERGABUNG MEMBERSHIP ALL-ACCOR LIVE LIMITLESS : Analysis of the Influence of Digital Promotions and Loyalty Discounts on Interest in Joining the All-Accor Live Limitless Membership - Rani, Ni Kadek Adi Maha; Santra, I Ketut; Yasa, Gede Sedana Wibawa (Ganec Swara, 2025)
The number of All Accor Live Limitless members staying at Sofitel Bali Nusa Dua Beach Resort has shown an increasing trend every year. This study aims to analyze the influence of digital promotions and loyalty discounts on the interest in joining the All Accor Live Limitless membership. This research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents selected through purposive and snowball sampling techniques. Data were collected both online and offline. Regression analysis results show that digital promotions and loyalty discounts simultaneously have a positive and significant effect on the interest in joining the membership, with an F value of 33.702 and significance < 0.05. Partially, digital promotions (t = 5.917) and loyalty discounts (t = 3.348) also have a significant effect, although loyalty discounts have a greater practical effect with a regression coefficient of 0.011 compared to digital promotions at 0.003. The resulting regression model explains 71.8% of the variation in the interest to join the membership. These findings emphasize that optimizing digital promotions and loyalty programs is crucial to increasing membership, especially in the hospitality industry in tourist destinations such as Bali.